Ethno-learning as a character education strategy: integration of local culture in cirebon schools - Cahyaningsih, Ade; Nurdin, Encep Syarief; Budimansyah, Dasim; Ruyadi, Yadi (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study aims to examine the implementation of ethno-learning as a character education strategy through the integration of local Kacirebonan cultural values in government-based secondary schools in Cirebon City. Using a multi-site ethnographic approach, this study was conducted for one year in four schools that actively develop culture-based learning. The results of the study indicate that ethno-learning is implemented in two main forms, namely through the integration of local culture in intracurricular subjects and through extracurricular activities such as mask dance, gamelan, rebana, and the "Jelajah Budaya" program. One important finding is the role of teachers as cultural mediators who bridge traditional values with the formal education process. Teachers not only act as teachers, but also as value facilitators, art trainers, and cultural preservation agents in schools. The implementation of ethno-learning has been proven to strengthen students' positive dispositions towards local culture, form humanistic social attitudes, and foster reflective cultural identities. This study concludes that culture-based education should not be a complement, but rather the main foundation in the formation of students' character in a contextual and sustainable manner